In-hospital severe COVID-19 in a philanthropic tertiary hospital setting: is asthma a concern? A retrospective study - Rojas, Gabriela Accetta; Ost, Flávia Nascimento; Stirbulov, Roberto; Simões, Ozíris (São Paulo Medical Journal, 2022)
BACKGROUND: The frequency of coronavirus disease 2019 (COVID-19) cases among asthmatics has been reported to be reduced. However, the findings regarding the association between asthma and the risk of severe COVID-19 have been divergent. OBJECTIVE: To investigate whether asthma is associated with a reduced risk of development of severe COVID-19. DESIGN AND SETTING: Retrospective analysis on COVID-19 surveillance databases at two tertiary-level hospitals in São Paulo, Brazil. METHODS: The medical records of patients hospitalized due to COVID-19 between March and August 2020 were reviewed in accordance with the clinical, laboratorial, radiological and epidemiological criteria for COVID-19, and for comorbidities. RESULTS: Among the adult patients included (> 18 years of age) there were 52 asthmatics and 1,318 non-asthmatics. Their median ages and interquartile ranges (IQR) were, respectively, 54 (41-69) and 60 (44-72) years. At least one comorbidity was seen in 73% of asthmatics and 56% of the non-asthmatics. Among the asthmatics, most presented mild asthma (92%) and the prevalence of chronic obstructive pulmonary disease (COPD) was high (27%). The asthmatics presented an unadjusted odds ratio (OR) for severe COVID-19 of 0.89 (95% confidence interval, CI 0.5-1.56); and OR 0.88 (95% CI 0.5 -1.68) after multivariable adjustment. Age > 60 years, male sex, hypertension, diabetes, cancer and homelessness were covariates associated with increased odds for severe COVID-19. Kaplan-Meier estimated survival over hospitalization of up to 30 days did not differ between the groups (log-rank P = 0.09). CONCLUSIONS: The association between asthma and decreased risk of severe COVID-19 or increased survival was statistically non-significant.